2018
DOI: 10.1111/ans.14713
|View full text |Cite
|
Sign up to set email alerts
|

Management of primary spontaneous pneumothorax: a review

Abstract: Primary spontaneous pneumothorax is a common problem faced by doctors in medical practice. It is a significant global health problem affecting adolescent and young adults. This article will review the etiopathology, diagnosis and current management guidelines. It aims to improve clinical practice and compliance to the complexities of procedures involved in management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Pneumothorax is a common thoracic disorder involving an abnormal collection of air in the space between the lungs and the chest wall 1 . A large volume of air in the pleural cavity can lead to tension pneumothorax, which compress the lungs and heart, causing shock and often death 2 . Therefore, it is important to check for the presence or absence of pneumothorax by taking a chest X-ray when a patient complains of chest pain and dyspnea.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumothorax is a common thoracic disorder involving an abnormal collection of air in the space between the lungs and the chest wall 1 . A large volume of air in the pleural cavity can lead to tension pneumothorax, which compress the lungs and heart, causing shock and often death 2 . Therefore, it is important to check for the presence or absence of pneumothorax by taking a chest X-ray when a patient complains of chest pain and dyspnea.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown numerous approaches offered by different guidelines and associations. According to the American College of Chest Physicians (ACCP), the British Thoracic Society (BTS), and the Spanish Society of Pulmonology and Thoracic Surgery, the initial management of the primary spontaneous pneumothorax is directed to remove air from the pleural space and prevent recurrences [1,38]. Treatment options for primary spontaneous pneumothorax go from simple observation, aspiration with a catheter, insertion of a chest tube, pleurodesis, thoracoscopy, video-assisted thoracoscopic surgery (which is one of the most studied approaches) to thoracotomy.…”
Section: Treatmentmentioning
confidence: 99%
“…Pneumothorax is defined as an abnormal collection of air in the pleural cavity, which is a potential space between the two pleurae (visceral and parietal) of the lungs [1]. Itard, a student of Laennec, first coined pneumothorax in 1803, but it was not until 1932 that it was realized that spontaneous pneumothorax was not always caused by tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…The approach to managing of catamenial pneumothorax is multi-faceted often involving a respiratory physician, thoracic surgeon, gynaecologist, radiologist and histopathologist 3,6,10,13,14 . In the first instance of spontaneous pneumothorax in clinically stable patients with small catamenial pneumothorax (<2-3cm on CXR), patients should be observed over ≥ 6 hours period, given high flow oxygen to aid resorption of pleural air, have a repeat CXR prior to discharge, as well as an outpatient appointment in 2-4 weeks 25 . Moderate-large catamenial pneumothorax requires needle aspiration or chest tube insertion and longer duration of hospital stay 15 .…”
Section: Imagingmentioning
confidence: 99%